Delirium management in perioperative geriatric services: a narrative review of non-pharmaceutical strategies - Travers, Rozenn; Gagliardi, Geoffroy; Ramseyer, Maximilian (Frontiers in Psychiatry, 2024)
Delirium, a common complication in elderly surgical patients, poses significant challenges in perioperative care. Perioperative geriatric services (PGS) aim at managing comorbidities, postoperative complications, and initiating early recovery of mobility to enhance elderly patients' prognosis in the perioperative period. Studies have shown that patients with preoperative cognitive disorders are at a significantly increased risk of postoperative delirium. While postoperative delirium affects up to 70% of people over 60 and 90% of people with neurodegenerative diseases, it remains underdiagnosed in many cases. Postoperative delirium can lead to functional decline, prolonged hospitalization, increased healthcare costs, cognitive impairment, and psychological malaise. This article briefly summarizes the literature on delirium, its risk factors, and its non-pharmaceutical management strategies within the perioperative period. It highlights the importance of integrating cognitive and psychological assessments into perioperative care protocols to provide baseline data, improve patient outcomes, reduce hospital stays, and minimize complications associated with delirium. By embracing evidence-based delirium management protocols, healthcare professionals can better identify and manage delirium, ultimately improving the quality of care for elderly surgical patients, which would also benefit healthcare staff and healthcare institutions.